2010
DOI: 10.1074/jbc.m109.041038
|View full text |Cite
|
Sign up to set email alerts
|

The Cdc42-interacting Protein-4 (CIP4) Gene Knock-out Mouse Reveals Delayed and Decreased Endocytosis

Abstract: The newly described F-BAR (Fer/CIP4 and Bin, amphiphysin, Rvs) family of proteins includes Cdc42-interacting protein-4 (CIP4), formin-binding protein-17 (FBP-17) and transactivator of cytoskeletal assembly-1 (Toca-1), and drives membrane deformation and invagination. Membrane remodeling affects endocytosis, vesicle budding, and cargo selection. The F-BAR family presents a novel family of proteins, which little is known about their in vivo function. We investigated the physiological role of CIP4, by creating Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
(42 reference statements)
3
47
0
Order By: Relevance
“…These data support an important role for F-BAR proteins in the regulation of membrane curvatures in a sequential manner during endocytosis (Suetsugu, 2010). Despite their pivotal functions in linking actin and membrane dynamics, recent single-knockout studies revealed that many F-BAR proteins are not essential for development and, thus, might have redundant or cooperative functions in vivo (Feng et al, 2010;Fricke et al, 2009). In fission yeast, the Cip4-like F-BAR proteins Cdc15 and Imp2 are examples for such synergistic function of two F-BAR proteins.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These data support an important role for F-BAR proteins in the regulation of membrane curvatures in a sequential manner during endocytosis (Suetsugu, 2010). Despite their pivotal functions in linking actin and membrane dynamics, recent single-knockout studies revealed that many F-BAR proteins are not essential for development and, thus, might have redundant or cooperative functions in vivo (Feng et al, 2010;Fricke et al, 2009). In fission yeast, the Cip4-like F-BAR proteins Cdc15 and Imp2 are examples for such synergistic function of two F-BAR proteins.…”
Section: Discussionsupporting
confidence: 55%
“…However, our understanding of how F-BAR proteins function in vivo in a physiological context is still incomplete because loss-offunction studies in higher organisms are limited. Mice that lack Cip4 are viable and show only a weak endocytosis defect of the insulin-responsive glucose transporter Glut4 (Feng et al, 2010). Mutant animals also display a reduced platelet production and defective integrin-dependent T-cell adhesion, both defects are probably caused by decreased WASP-dependent actin polymerization, rather than impaired endocytosis (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…CIP4-knockout mice are viable, but have altered glucose metabolism (Feng et al, 2010). This is consistent with cell-based studies implicating CIP4 in regulating both the trafficking of GLUT4 storage vesicles to the plasma membrane (Lodhi et al, 2007), as well as GLUT4 endocytosis via CIP4 interactions with N-WASP and dynamin-2 (Hartig et al, 2009).…”
Section: Introductionsupporting
confidence: 83%
“…The N-WASP-WIP complex, together with Toca-1 or FBP17, activates actin polymerization on phosphatidylserinecontaining membranes (Takano et al, 2008). These roles have been confirmed with the observation that mouse Cip4-null cells have delayed and decreased endocytosis (Feng et al, 2010).…”
Section: Actin Polymerization Ii: Wasp and Wave Complexes Initiate Brmentioning
confidence: 63%